Ramadan For Sale: A Semiotic Analysis of Ramadan Fashion Bazaar Promotion on Social Media - Muhammad Fachri Shandika Iman (Dinasti Publisher, 2025)
This study explores how the promotion of Muslim fashion bazaars during Ramadan serves as a medium for reproducing consumerist ideology on social media. The object of this research is the promotional content of Glamlocal Wonderful Ramadan 2025, published on Instagram and TikTok. The study aims to understand how capitalism appropriates religious symbols to construct new meanings of the Ramadan celebration. The method employed is digital text analysis using Roland Barthes’ semiotic approach, focusing on the construction of meaning through signs (signifier and signified) at both denotative and connotative levels, as well as the formation of myths within specific social and cultural contexts. The analyzed promotional content was posted by the @glamlocal.id account and features consumerist narratives encouraging consumption during Ramadan. The findings reveal that religious narratives in these promotional contents have been recontextualized into consumerist imagery that emphasizes material gratification and symbolic identity. This phenomenon risks shifting the meaning of Ramadan from a period of spiritual reflection into a legitimized consumption ritual marked by religious symbols. These findings highlight the dominance of sign logic in modern consumer society and underline the urgent need for critical awareness of the manipulation of religious symbols by capitalist forces.